Carbon Capture: Visible Light Triggered CO2 Liberation from Silver Nanocrystals Incorporated Metal–Organic Frameworks (Adv. Funct. Mater. 27/2016). (19th July 2016) - Li, Haiqing; Hill, Matthew R.; Doblin, Christian; Lim, Seng; Hill, Anita J.; Falcaro, Paolo
Abstract : H. Li, P. Falcaro, and coworkers describe on page 4815 the development of a new photodynamic Metal‐Organic Framework (MOF) composite that exhibits up to 90.5% of CO2 desorption capacity under the irradiation of naturally abundant visible light. Their discovery is promising for the application of MOFs in carbon capture as a route to low‐energy regeneration of gas adsorbents.